2019
DOI: 10.1242/jeb.203455
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FABP knockdown on flight performance of the desert locust, Schistocerca gregaria

Abstract: During migratory flight, desert locusts rely on fatty acids as their predominant source of energy. Lipids mobilized in the fat body are transported to the flight muscles and enter the muscle cells as free fatty acids. It has been postulated that muscle fatty acid-binding protein (FABP) is needed for the efficient translocation of fatty acids through the aqueous cytosol towards mitochondrial β-oxidation. To assess whether FABP is required for this process, dsRNA was injected into freshly emerged adult males to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The mediating role played by FABP in ACP-controlled flight-related lipid metabolism was further confirmed by knockdown and rescue experiments at the molecular, metabolic, and behavioral levels. The significant role of FABP in prolonged flight has also been reported in the desert locust (Rajapakse et al, 2019), indicating that FABP plays a conserved role in lipid metabolism and long-term flight in locust species.…”
Section: Fabp Acts As a Key Molecule For Flight-related Energy Metabolism Underlying Acp Modulationmentioning
confidence: 69%
“…The mediating role played by FABP in ACP-controlled flight-related lipid metabolism was further confirmed by knockdown and rescue experiments at the molecular, metabolic, and behavioral levels. The significant role of FABP in prolonged flight has also been reported in the desert locust (Rajapakse et al, 2019), indicating that FABP plays a conserved role in lipid metabolism and long-term flight in locust species.…”
Section: Fabp Acts As a Key Molecule For Flight-related Energy Metabolism Underlying Acp Modulationmentioning
confidence: 69%
“…Studies have indicated that fatty acid metabolism is an important metabolic mode for long-distance migration of insects ( Arrese and Soulages, 2010 ; Guo et al, 2022 ), combined with the pattern of flight muscle histolysis after migration ( Feng et al, 2019 ), it can be inferred that compared with other metabolic pathways, fatty acid metabolic pathway is more likely to be a regulatory pathway involved in and regulating flight muscle histolysis, and fatty acid transporters are more likely to act as regulatory signals than other proteins with fixed metabolic functions due to their properties of transporting fatty acids. In addition, it is reported that FABP has also been reported to be crucial for long-distance migration of migratory locusts ( Rajapakse et al, 2019 ). That is the reason why this study finally focused on it for research.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of AdomFABP gene expression promotes this process in A. domesticus . FABP has been reported to play an important role in lipid uptake and transport in locust flight muscle and is an essential element of skeletal muscle metabolism involved in sustained muscle activity, the absence of which prevents locusts from migrating long distances ( Rajapakse et al, 2019 ). Increased FABP levels are associated with the flight ability of insects ( Haunerland, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…In both desert locust Schistocerca gregaria (Orthoptera: Acrididae) and L. migratoria , the flight duration of individuals was significantly shortened after FABP gene expression was silenced. The flight distance of L. migratoria was also significantly decreased [ 14 , 148 ], mainly due to the silencing of the FABP gene, which seriously affects the oxidative metabolism of fatty acids in the flight muscle during sustained flight. FFA are catalyzed by fatty acyl-coenzyme A on the outer mitochondrial membrane to produce fatty acyl A, which is then transported to the mitochondrial matrix by carnitine palmitoyltransferase (CPT) in the inner and outer membranes of mitochondria [ 136 , 149 , 150 ].…”
Section: Energy and Substance Metabolism During Insect Migration Flightmentioning
confidence: 99%